Diagnostic value of R wave in aVL lead in left ventricular hypertrophy - Daniel Alejandro Denis-Piedra; Sheila Martínez-Gutiérrez; Albert Ramón Figueredo-Gilbert; Elia de la Caridad Rodríguez-Venegas (Universidad Médica Pinareña, 2020)
Introduction: left ventricular hypertrophy (LVH) is defined as the increase in the thickness of the wall or the interventricular septal portion (or both). This entity represents an important risk factor that is related to the increase in mortality. Its diagnosis is based on voltage criteria that become visible on the is based on voltage criteria that become visible on the electrocardiogram, such as that the R-wave voltage criterion in lead aVL (RaVL).